TINDAK TUTUR ESKPRESIF DALAM FILM SEKAWAN LIMO KARYA BAYU SKAK (KAJIAN PRAGMATIK) - Dista Melanise; I Wayan Letreng; Sri Yanuarsih (Jurnal Bastra (Bahasa dan Sastra), 2025)
Speech acts are part of the study of pragmatics, which discusses how utterances not only convey information but also act as social actions. One such form is expressive speech acts, which are utterances used to express the speaker’s feelings or attitudes toward a situation. Film, as a communication medium that combines visual and verbal elements, is a relevant tool for analyzing language use in real life contexts. This study examines the forms of expressive speech acts in Bayu Skak’s film Sekawan Limo, which tells the story of five friends Bagas, Lenni, Juna, Dicky, and Andrew as they experience a terrifying experience while climbing Mount Madyopuro and debunking local myths. The method used is descriptive qualitative, with data collection techniques including documentation, literature review, reading, and recording techniques. The primary data consists of dialogues between characters containing three types of expressive speech acts: sarcasm, mockery, and complaint. The results show that these six forms appear in various conversational contexts, reflecting the emotional expressions and social relationships between characters, which are communicatively represented in the film.